Ghana : Second Review Under the Extended Credit Facility Arrangement and Request for Waiver for Nonobservance of Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Ghana. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses Ghana's Second Review Under the Extended Credit Facility Arrangement and Request for Waiver for Nonobservance of Performance Criterion (PC). Program implementation has been broadly satisfactory to date, but the economic outlook remains difficult, and risks are tilted to the downside. All PCs were met at end-August 2015, with the exception of the continuous PC on nonaccumulation of external arrears, which was not observed owing to some small payments delays. The IMF staff supports the authorities' request for a waiver for this, given the corrective actions that will be implemented to avoid new external arrears. The IMF staff recommends completion of the second review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet